Prediction of the adherence to sports practice of young Ecuadorians based on the perception of the coach’s interpersonal style - Heredia-León, Diego Andrés; Manzano-Sánchez, David; Gómez-Mármol, Alberto; Valero-Valenzuela, Alfonso (Frontiers in Psychology, 2023)
Based on the framework of the self-determination theory, the present study aimed to test in the Ecuadorian sports context a predictive model using autonomy support as a trigger, which is mediated by basic psychological needs and later by autonomous motivation, to predict the intention to be physically active. It was carried out on 280 athletes from the province of Azuay (Ecuador) aged between 12 and 20 years (M = 15.28; SD = 1.71). Different scales were used to measure the perception of the interpersonal style of autonomy supported by the coach, the satisfaction of basic psychological needs, the motivation towards sports practice, and the intention to be physically active. Structural equation analysis revealed that perceived autonomy support positively predicted basic psychological needs, which in turn positively predicted autonomous motivation, and these ultimately the athletes' intention to be physically active. It is concluded that the interpersonal style of autonomy support by coaches can benefit the development of basic psychological needs and with it autonomous motivation, generating an increase in the intention to be physically active in young athletes. Future research is suggested to verify this predictive model, as well as to carry out experimental studies in which coaches promote autonomy support for their athletes intending to increase adherence to sports practice.